Confirmation of Intimal Tear in Thrombosed-Type Acute Aortic Dissection by Virtual Angioscopy. (2016) - Cho, T.; Tokunaga, S.; Izubuchi, R.; Masuda, M.
Abstract : Introduction: Therapeutic strategies for intramural hematoma (IMH) involving the ascending aorta remain controversial. Report: The patient was a 72 year old woman with a history of chest pain. Multidetector computed tomography (MDCT) showed an IMH involving the ascending aorta. Because virtual angioscopy revealed a punctate intimal tear in the ascending aorta, acute aortic dissection with an intimal tear and not IMH was diagnosed, and emergency surgery was performed. The post-operative course was uneventful. Discussion: Virtual angioscopy allows the vascular lumen to be examined minimally invasively on the basis of images reconstructed from MDCT data. Even if MDCT does not clearly show an intimal tear associated with aortic dissection in a general view, virtual angioscopy can show the exact location and size of the tear before surgery. Virtual angioscopy is very useful for distinguishing thrombosed-type acute aortic dissection without clear ulcer like projections from an IMH, which may facilitate therapeutic planning.